Effect of Standard Operating Procedures (SOP) and Work Environment on Employee Performance of PT. Bank Perkreditan Rakyat Sulawesi Mandiri Makassar - M. Fahrul Husni; Mattarima; Suljumansah; Vebby Anwar; Devid (PT FORMOSA CENDEKIA GLOBAL, 2023)
In general, most companies believe that to achieve success, they must strive for the maximum possible performance, both individual and group performance which ultimately affects the success of the company (Purwadi, 2017). The success that every company wants is not far from how managers manage Human Resource Management, in this case employee performance is the main capital to achieve a company success. As Standard Operating Procedures (SOP) play a role in making it easier for companies to organize and carry out the workflow or implementation of a task and as a guide for work results to achieve desired goals, (Arnina, 2016). For this reason, the purpose of this study is to determine the influence of standard operating procedures (SOP) and work environment on the performance of PT. People's Credit Bank Sulawesi Mandiri Makassar. Metode analysis used is multiple linear regression analysis using the SPSS application by looking at the constant value and the value of the resulting remission coefficient. The results of the analysis show that standard operating procedures (SOP) and work environment have a positive and significant effect on the performance of PT. People's Credit Bank Sulawesi Mandiri Makassar